Analysis of strength size effect and failure mechanism of asphalt mixtures based on discrete element method - Pei Zhao; Shenghua Shi; Weiwei Lu; Songtao Lv; Qi Chen; Haihui Duan; Yi Yang (Case Studies in Construction Materials, 2024)
The purpose of this study is to further investigate the strength size effect and failure mechanism of asphalt mixtures and clarify the strength parameter conversion relationship between standard and non-standard size samples. The article established an improved microscopic model for uniaxial compression and indirect tensile testing of asphalt mixtures based on laboratory and discrete element simulation tests. The effects of thickness and gradation on the uniaxial compressive strength (UCS) and indirect tensile strength (ITS) of asphalt mixtures were studied. The loading rates of the UCS and ITS tests were set at 2 mm/min and 50 mm/min, respectively. Additionally, the tensile-compressive stress distribution, crack propagation, and strength contribution rates of different contact types within the sample were investigated during the virtual model loading process. The reliability of the model was validated through laboratory test results. Finally, the strength parameter conversion relationship between standard and non-standard size samples was investigated. The study found that the UCS of asphalt mixtures decreases with increasing thickness, while the ITS increases with increasing thickness, with average reduction and increase rates of 70.69 % and 24.18 %, respectively. The contact fracture ratio and the strength contribution rate of the aggregate-asphalt mortar contacts both exceed 50 %, indicating that the fracture of these contacts is the primary cause of asphalt mixture failure. The use of small-sized samples instead of standard samples in practical applications is promising. These research work outcomes can serve as a theoretical basis for designing asphalt pavement materials and acquiring existing asphalt pavement material parameters.